UNIT-NET IEDI: AN INFRASTRUCTURE FOR ELECTRONIC DATA INTERCHANGE - Ermolayev, V.A.; Spivakovsky, A.V; Zholtkevych, G.N.; Bulat, A.V.; Keberle, N.G. (Journal of Information Technologies in Education (ITE), 2007)
The paper presented the reference architecture of Infrastructure for Electronic Data Interchange. IEDI is the multi-layered distributed intelligent software system comprising software servers, services, components and tools providing intelligent ontology-driven information retrieval from distributed, heterogeneous, legally and physically autonomous Informational Resources (Irs) for the organizational network of the Ukrainian National Higher Education System.